Performace Measurement of Intellectual Capital - Grigoryan, Ani (2023)
The aim of this thesis is to review the existing measurement methods of intellectual capital and assess the effect intellectual capital has on a firm’s financial performance. It is structured into theoretical and practical sections. The theoretical part includes an extensive literature review on intellectual capital types and measurement methods. The practical part presents a statistical analysis, determining how intellectual capital influences a company’s financial performance. This analysis utilizes five years of data from 880 firms across various sectors and countries. The findings indicate a positive correlation between certain intellectual capital components and financial performance, with industry-specific differences observed.